AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND ON THE TENTH GRADE STUDENTS' WRITING PERSONAL LETTER IN SMA NEGERI 1 SIANTAR - Gultom, Elisabeth Morauli; Hutauruk, Bertaria Sohnata; Nababan, Irene Adryani (English Education Department at FKIP Nommensen University, 2024)
This research presents the figurative language used by students in writing personal letters at SMA Negeri 1 Pematangsiantar. The aim of this research was to determine the types of figurative language students use when writing personal letters. The focus of this research is stated by the researcher as follows: the kinds of figurative language used by students in writing personal letters and the dominance of figurative language used by students in writing personal letters. This research uses qualitative descriptive research methods, and used an essay test to gather the data. This research used the research subject and took 35 out of 36 students. The researcher discovered four types of figurative language used by students in writing personal letters. They are: Metaphor 10 sentences (27,03%), 10 Simile (27,033%), Personification 9 sentence (24,32%), Hyperbole 8 sentences (2.62%). Letters play a vital role as a medium to convey our feelings, ideas, and ideas that create the best effect in developing understanding or imagination in choosing and arranging words, especially if the word uses figurative language to refresh and be colorful in its presentation.